2021
DOI: 10.1101/2021.11.13.468472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A live attenuated influenza virus-vectored intranasal COVID-19 vaccine provides rapid, prolonged, and broad protection against SARS-CoV-2 infection

Abstract: Remarkable progress has been made in developing intramuscular vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); however, they are limited with respect to eliciting local immunity in the respiratory tract, which is the primary infection site for SARS-CoV-2. To overcome the limitations of intramuscular vaccines, we constructed a nasal vaccine candidate based on an influenza vector by inserting a gene encoding the receptor-binding domain (RBD) of the spike protein of SARS-CoV-2, named… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“… 20 Data from the preclinical study of dNS1-RBD showed that lung-resident memory RBD-specific CD4 + and CD8 + T cells could be induced by vaccination, and the T-cell immune response produced in lung tissue was about 26-times stronger than that in PBMCs in mice immunised with a single dose. 10 Nevertheless, it is difficult to observe the immune response in the lungs in clinical trials when human lung sampling is impractical, which might lead to underestimation of the intensity of cellular immunity of such vaccines clinically.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 20 Data from the preclinical study of dNS1-RBD showed that lung-resident memory RBD-specific CD4 + and CD8 + T cells could be induced by vaccination, and the T-cell immune response produced in lung tissue was about 26-times stronger than that in PBMCs in mice immunised with a single dose. 10 Nevertheless, it is difficult to observe the immune response in the lungs in clinical trials when human lung sampling is impractical, which might lead to underestimation of the intensity of cellular immunity of such vaccines clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the levels of several cytokines or chemokines, including those from innate and adaptive immune responses, were significantly altered in the lung tissues of mice after dNS1-RBD immunisation in the preclinical study. 10 Additionally, vaccine-induced innate responses have been shown to be protective against viral infection in several studies. An important limitation of our study is the absence of an evaluation of local immune responses in humans, both innate and acquired immune responses; which might support the findings in animal studies that dNS1-RBD can act rapidly in the upper respiratory tract or nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations